2007
DOI: 10.1126/science.1140461
|View full text |Cite
|
Sign up to set email alerts
|

155,000 Years of West African Monsoon and Ocean Thermal Evolution

Abstract: A detailed reconstruction of West African monsoon hydrology over the past 155,000 years suggests a close linkage to northern high-latitude climate oscillations. Ba/Ca ratio and oxygen isotope composition of planktonic foraminifera in a marine sediment core from the Gulf of Guinea, in the eastern equatorial Atlantic (EEA), reveal centennial-scale variations of riverine freshwater input that are synchronous with northern high-latitude stadials and interstadials of the penultimate interglacial and the last deglac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

36
391
2
4

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 417 publications
(433 citation statements)
references
References 43 publications
36
391
2
4
Order By: Relevance
“…This enhancement is also found in records from northern Africa and South America and shown in Fig. 1a by the anti-phasing of the north African humidity index of Tjallingii et al (2008) and Gulf of Guinea sea surface salinity reconstruction of Weldeab et al (2007) with the South American cave records of Wang et al (2004Wang et al ( , 2007, Cruz et al (2005) and Bolivian salt flat sediment core of Fritz et al (2004). The much-studied African Humid Period, during which grass and low shrub vegetation expanded northward into the Sahel-Sahara region, coincides with a maximum in NH summer insolation (Gasse 2000;DeMenocal et al 2000).…”
Section: Comparison With Proxy Recordsmentioning
confidence: 58%
See 1 more Smart Citation
“…This enhancement is also found in records from northern Africa and South America and shown in Fig. 1a by the anti-phasing of the north African humidity index of Tjallingii et al (2008) and Gulf of Guinea sea surface salinity reconstruction of Weldeab et al (2007) with the South American cave records of Wang et al (2004Wang et al ( , 2007, Cruz et al (2005) and Bolivian salt flat sediment core of Fritz et al (2004). The much-studied African Humid Period, during which grass and low shrub vegetation expanded northward into the Sahel-Sahara region, coincides with a maximum in NH summer insolation (Gasse 2000;DeMenocal et al 2000).…”
Section: Comparison With Proxy Recordsmentioning
confidence: 58%
“…1 a Paleorecords of tropical hydroclimate against the precessional cycle (e sin(ω), see Sect. 2; grey); from top to bottom: composite of speleothem δ 18 O from Chinese caves (25°-32°N): Dongge (Dykoski et al 2005), Hulu (Wang et al 2004), Sanbao (Wang et al 2008); North African humidity index 20.8°N (Tjallingii et al 2008); sediment total reflectance in Cariaco Basin 10.7°N (Deplazes et al 2013); salinity reconstruction from Ba/Ca in Eastern Atlantic (2.5°N) (Weldeab et al 2007); ln(Ti/Ca) from West Pacific Warm Pool (2.5°S) (Tachikawa et al 2014); sediment gamma radiation from Bolivia (20.3°S) (Fritz et al 2004); speleothem δ 18 O from Botuvera cave (Brazil; 27.2°S) (Wang et al 2004(Wang et al , 2007Cruz et al 2005). Records are ordered from north to south, with inferred precipitation increasing along the y-axis; A 1000-year running mean was applied to each record.…”
Section: Introductionmentioning
confidence: 99%
“…The abrupt change of this arid phase towards more moist conditions during the later terminations is also characteristic for glacial-interglacial transitions in general, and is the result of geographical shifts and intensifications changes within the West African Monsoon system (Balsam et al, 1995;Pflaumann et al, 1998;Tjallingii et al, 2008). Like in the early Holocene monsoon intensification over NW Africa during the early phase of MIS 11c was probably related to a northward-moving ITCZ, which caused a weakening of the trade winds and, accordingly, a decrease in coastal upwelling intensity (Adkins et al, 2006;Weldeab et al, 2007). Due to the combined effects of vegetation cover/enhanced precipitation and diminished trade wind strength, total dust flux off NW Africa is reduced when North Atlantic SSTs rise and vice versa (e.g., Tjallingii et al, 2008).…”
Section: Dynamics Of Sea-surface Properties In the Lower Latitudesmentioning
confidence: 99%
“…Several recent studies have demonstrated that Ba/Ca shell in foraminifera from marine environments proximal to riverine outflow can be used as an independent proxy for reconstructing paleosalinity (Hall and Chan, 2004;Plewa et al, 2006;Sprovieri et al, 2008;Weldeab et al, 2007). The relationship between riverine Ba/Ca and salinity varies geographically.…”
Section: Planktic Foraminifer Ecology and Geochemistrymentioning
confidence: 99%
“…The relationship between riverine Ba/Ca and salinity varies geographically. Weldeab et al (2007) showed that Niger River Ba/Ca differs from the Amazon (Boyle, 1976) and the Ganges-Brahmaputra ( Fig. S-2a; Carroll et al, 1993).…”
Section: Planktic Foraminifer Ecology and Geochemistrymentioning
confidence: 99%